Subgrouping of Japanese middle-aged women attending a menopause clinic using physical and psychological symptom profiles: a cross-sectional study - Terauchi, Masakazu (BMC Womens Health, 2014)
BACKGROUND: Women in the menopausal transition and the postmenopausal period are affected with vasomotor symptoms, urogenital atrophy, sexual dysfunction, somatic symptoms, cognitive difficulty, sleep disturbance, and psychological problems. It is important to gain a better understanding of the complexity and diversity of climacteric disturbance in order to optimize treatments for individual patients. The aim of this study was to identify subgroups of Japanese perimenopausal and postmenopausal women attending a menopause clinic based on their physical and psychological symptom profiles. METHODS: We administered the Menopausal Health-Related Quality of Life questionnaire to 491 Japanese women aged 40–64 years who had enrolled in the Systematic Health and Nutrition Education Program at the Menopause Clinic of the Tokyo Medical and Dental University Hospital between 2005 and 2012. We performed a principal component analysis followed by a hierarchical cluster analysis of the responses to 9 physical and 12 psychological items on the questionnaire. RESULTS: The first analysis extracted 3 principal components that defined the variance of physical and psychological symptom profiles: depression, somatic, and vasomotor/sleep. A subsequent cluster analysis was performed based on the 3 principal components to generate 4 clusters, CL8 (N = 162; 33.0%), CL6 (N = 111; 22.6%), CL5 (N = 102; 20.8%), and CL4 (N = 116; 23.6%). CL8 included women who only had mild-to-moderate musculoskeletal pains and tiredness. All women in CL6, CL5, and CL4 described their musculoskeletal pains and tiredness as moderate to severe. The women in CL5 also had moderate-to-severe vasomotor symptoms, while the women in CL4 also suffered from moderate-to-severe psychological symptoms, such as depression, anxiety, and insomnia. CONCLUSIONS: Distinct subgroups of Japanese perimenopausal and postmenopausal women were identified based on their symptom profiles. Menopausal symptoms were shown to accumulate in this population in the order of musculoskeletal pains and tiredness, vasomotor symptoms, and psychological symptoms.